Missio Dei dan Keadilan Sosial: Telaah Misiologis tentang Peran Gereja dalam Menghadapi Krisis Ketidakadilan Hak Asasi Manusia - Elizabeth Liliek Rusiati; Sandy Tejalaksana; Hari Winarko; Agustina Pasang (Sekolah Tinggi Teologi Injili Efrata Sidoarjo, 2025)
This article examines the role of the church within the framework of the Missio Dei in responding to the crisis of human rights injustices in Indonesia, highlighting key issues such as the prevalence of discrimination, structural violence, and the weak protection of vulnerable groups. The purpose of this study is to explain the theological foundations while offering practical and applicable strategies that the church can implement in addressing these situations. The method employed is a literature study using a descriptive qualitative approach. The findings indicate that the church must carry out a prophetic role through the voice of prophecy, a pastoral role by accompanying victims, and an educative role through human rights education. In addition, the outlined practical strategies include public advocacy and policy engagement, empowerment programs for vulnerable groups through training, thematic liturgy and social education, as well as concrete solidarity through interfaith peace actions and the establishment of crisis centers for victims.